PENGARUHIPENERAPANIMODELIPEMBELAJARANEKOOPERATIFQTIPEIFORMULATEISHAREILISTENIANDECREATEETERHADAPYKEMAMPUANFKOMUNIKASICMATEMATISDPESERTAFDIDIKDKELASDXIRIPA SMAHADABIAHRPADANG - Dwi Hidayatul Fitri (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical communication skills of grade XI IPA Adabiah Padang high school students are still low. This is because the learning process is not optimal in improving students' mathematical communication skills. One effort that can be done to improve students' mathematical communication skills is by applying the formulate Share Listen and Create (FSLC) cooperative learning model. The purpose of this study was to investigate whether the mathematical communication skills of students who learn to use the FSLC type of cooperative learning model are better than the mathematical communication skills of students who learn with conventional learning.Keywords — Formulate Share Listen and Create, Mathematical Communication Skills.